Detecting degradation in reinforced concrete subjected to uniaxial compression, using the parameters of electric response to mechanical impact; Research in Nondestructive Evaluation; Vol. 30, iss. 6 - Fursa T. V. Tatyana Viktorovna; Utsyn G. E. Grigoriy Evgenievich; Petrov M. V. Maksim Vyacheslavovich; Dann D. D. Denis Dmitrievich; Sokolovsky A. N. Aleksey Nikolaevich (2018, 2018)
Title screen